Systematic review of electronic remote blood issue. Issue 1 (31st March 2015) - Sellen, K. M.; Jovanovic, A.; Perrier, L.; Chignell, M.
<x xml:space="preserve">Abstract</x> Background and Objectives The implementation of electronic remote blood issue (ERBI) may provide safety and efficiency gains for transfusion medicine. This systematic review's objective was to assess whether ERBI affects incidents of adverse events, time taken for blood issue and delivery, and cross‐match to transfusion ratios, among other measures of safety and efficiency. The review also sought to uncover barriers and facilitators of ERBI implementation. Materials and Methods We searched four aggregated electronic databases (Medline, EMBASE, CINAHL and BIOSIS) up to 19 July 2012, with an updated search performed on 5 March 2014 for studies on ERBI. No specific study design criteria were used in the initial inclusion due to the low number of studies on ERBI. Results A total of 4758 citations were initially identified; after 1844 duplicates were removed, 2612 citations were excluded on the basis of the abstract. Two reviewers evaluated a total of 302 full‐text articles independently; of these, seven citations were eligible for inclusion. An updated search and the authors' own collections confirmed an additional five citations, totalling 13 citations and six studies within these. Conclusion There is insufficient evidence to demonstrate whether ERBI significantly impacts safety and efficiency of blood transfusion and delivery processes. Rigorously designed studies to assess safety and efficiency outcomes are required using proxy or corollary measures. A number of positive results were reported, however, and most studies included suggestions for facilitating ERBI implementation.